1999
DOI: 10.1177/002224379903600408
|View full text |Cite
|
Sign up to set email alerts
|

HINoV: A New Model to Improve Market Segment Definition by Identifying Noisy Variables

Abstract: Although cluster analysis is the procedure most frequently used to define data-based market segments, it is not without problems. This research addresses one of its major problems: the selection of the "best" subset of variables on which to cluster. If this selection is not made carefully, "noisy" variables that contain little clustering information can cause misleading results. To help isolate potentially noisy variables prior to clustering, the authors discuss a new algorithm, the Heuristic Identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Method 6: HINoV (Carmone et al, 1999) The HINoV clustering procedure developed by Carmone et al (1999) consists of the following steps:…”
Section: Methods 5: Projection Pursuitmentioning
confidence: 99%
See 2 more Smart Citations
“…Method 6: HINoV (Carmone et al, 1999) The HINoV clustering procedure developed by Carmone et al (1999) consists of the following steps:…”
Section: Methods 5: Projection Pursuitmentioning
confidence: 99%
“…Although Carmone et al (1999) recommend ranking the TOPRI(v) values in descending order and using a scree-type plot to determine the cutoff point for selected variables, this procedure is not computationally feasible for a large experimental study. Therefore, we formalized Carmone et al's method by using the ratio rule in Step 5.…”
Section: Methods 5: Projection Pursuitmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected Hubert and Arabie's (1985) adjusted Rand index as the measure of agreement between the consensus partition and the validation partitions. This decision was based on the well-recognized properties of the ARI in the classification literature (Steinley, 2004), as well as its importance in market segmentation research (Helsen and Green, 1991;Carmone et al, 1999). Simulation studies have shown that ARI is the most desirable index for measuring segment recovery (Steinley, 2004).…”
Section: Discussion Conclusion and Implications For Current Practicementioning
confidence: 99%
“…That said, DBSCAN is one of many fast, algorithmic, clustering methods. We considered a few to initialize C-MPPCA and formally compare DBSCAN to the one of the best methods reported in Steinley and Brusco (2008), heuristic identification of noisy variable (HINoV) (Carmone, Kara, and Maxwell 1999). As summarized in Section 5, DBSCAN outperforms HINoV.…”
Section: C-mppcamentioning
confidence: 99%